Favipiravir-Based Ionic Liquids as Potent Antiviral Drugs for Oral Delivery: Synthesis, Solubility, and Pharmacokinetic Evaluation - Moshikur, R.M. (American Chemical Society, 2021)
Coronavirus disease 2019 (COVID-19) has spread across the world, and no specific antiviral drugs have yet been approved to combat this disease. Favipiravir (FAV) is an antiviral drug that is currently in clinical trials for use against COVID-19. However, the delivery of FAV is challenging because of its limited solubility, and its formulation is difficult with common organic solvents and water. To address these issues, four FAV ionic liquids (FAV-ILs) were synthesized as potent antiviral prodrugs and were fully characterized by nuclear magnetic resonance (NMR) spectroscopy, Fourier-transform infrared (FT-IR) spectrometry, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), derivative thermogravimetry (DTG), and differential scanning calorimetry (DSC). The aqueous solubility and in vivo pharmacokinetic properties of the FAV-ILs were also evaluated. The FAV-ILs exhibited improved aqueous solubility by 78 to 125 orders of magnitude when compared with that of free FAV. Upon oral dosing in mice, the absolute bioavailability of the Î²-alanine ethyl ester FAV formulation was increased 1.9-fold compared with that of the control FAV formulation. The peak blood concentration, elimination half-life, and mean absorption time of FAV were also increased by 1.5-, 2.0-, and 1.5-fold, respectively, compared with the control. Furthermore, the FAV in the FAV-ILs exhibited significantly different biodistribution compared with the control FAV formulation. Interestingly, drug accumulation in the lungs and liver was improved 1.5-fold and 1.3-fold, respectively, compared with the control FAV formulation. These results indicate that the use of ILs exhibits potential as a simple, scalable strategy to improve the solubility and oral absorption of hydrophobic drugs, such as FAV. Â©